2019
DOI: 10.3846/transport.2019.9317
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ship Speed and Fleet Deployment Under Carbon Emissions Policies for Container Shipping

Abstract: In this paper, under the consideration of two carbon emissions policies, the issues of optimizing ship speed and fleet deployment for container shipping were addressed. A mixed-integer nonlinear programming model of ship speed and fleet deployment was established with the objective of minimising total weekly operating costs. A simulated annealing algorithm was proposed to solve the problem. An empirical analysis was conducted with the data selected from the benchmark suite. The applicability and effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The paper by Reference [95] analyzes more than 50 studies published from 2004 to 2015 in the fields of environmental sustainability, decision support systems and multi-objective optimization in maritime shipping. Most of the available studies propose mathematical models or computerized simulation for optimizing specific maritime operations: Among the others, fleet deployment [96,97], berth allocation [98], scheduling optimization and vessels routing [99][100][101]. A low-level operational problem regarding the optimization of vessel speeds and fleet size in response to ECA regulations is discussed in Reference [102].…”
Section: Management and Logistic Measuresmentioning
confidence: 99%
“…The paper by Reference [95] analyzes more than 50 studies published from 2004 to 2015 in the fields of environmental sustainability, decision support systems and multi-objective optimization in maritime shipping. Most of the available studies propose mathematical models or computerized simulation for optimizing specific maritime operations: Among the others, fleet deployment [96,97], berth allocation [98], scheduling optimization and vessels routing [99][100][101]. A low-level operational problem regarding the optimization of vessel speeds and fleet size in response to ECA regulations is discussed in Reference [102].…”
Section: Management and Logistic Measuresmentioning
confidence: 99%
“…They proposed that the emission control policies to reduce the port-related emissions, especially for the cargo-delivery transport phase from port to city, are key for large coastal port cities such as Shanghai. Although the existing literature investigated the optimization of ship speed [15], the approach to the evaluation of technology and capacity choices for ships [16], and renewable energy sources, clean fuels and measures of efficient energy use in ports [17], there are few studies in the literature concerning the impact of a cap-and-trade system on port and navigation from the perspective of the supply chain. While there is now a rich literature on the cap-andtrade scheme from the perspective of the product supply chain, surprisingly little work of this kind has studied and analyzed it from the perspective of port and navigation supply chains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lirn et al [29] indicated that a greener policy had a direct and positive influence on both the greener ships and the greener suppliers' factors. Xing et al [30] considered two carbon emission policies to explore the problem of container ship speed optimization and fleet scheduling. Zhu et al [31] investigated the potential impact of an open maritime emissions trading system (METS) on individual containership operators' fleet composition strategies and CO2 emissions levels.…”
Section: Literature Reviewmentioning
confidence: 99%